2015
DOI: 10.1038/srep16160
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Sleep Duration and Risk of Childhood Obesity: Systematic Review and Dose-response Meta-analysis of Prospective Cohort Studies

Abstract: A meta-analysis of cross-sectional studies found that shorter-time sleep was correlated with increased risk of obesity in children. However, findings from prospective cohort studies were inconsistent. PubMed and other data resources were searched through May 2015. Twenty-five eligible studies were identified including 56,584 children and adolescents with an average 3.4-year follow-up. Compared with children having the longest sleep duration (~12.2 hours), kids with the shortest sleep duration (~10.0 hours) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
87
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 57 publications
9
87
2
2
Order By: Relevance
“…Our findings are consistent with previous studies that have also found that less sleep in children is associated with greater body weight (2, 3, 5). However, our observation that there was collinearity with parent reported school night sleep duration emphasizes the importance of obtaining adequate sleep during the week.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with previous studies that have also found that less sleep in children is associated with greater body weight (2, 3, 5). However, our observation that there was collinearity with parent reported school night sleep duration emphasizes the importance of obtaining adequate sleep during the week.…”
Section: Discussionsupporting
confidence: 93%
“…One recent review and one meta-analysis have also shown a clear association between short sleep duration and an increased risk of childhood obesity, however, very few studies in this meta-analysis included children less than 5 years of age2930. The present study found an inverse association between sleeping time and the risk of hyperglycemia, which supported the previous finding31.…”
Section: Discussionsupporting
confidence: 89%
“…As shown in Table , we identified 12 unique meta‐analyses of observational studies investigating associations of risk factors for obesity in children and adolescents, which were derived from 11 unique references, plus one that failed to show any nominally significant (ie P < 0.05) associations of weight gain during pregnancy and obesity during both childhood and adulthood.…”
Section: Resultsmentioning
confidence: 99%